(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In an era of unparalleled connectivity, international internet publications hold immense power to shape global narratives and influence public opinion. Among the most pressing concerns of our time, environmental problems demand urgent attention and concerted global efforts. This article delves into the coverage of environmental issues by international internet publications, aiming to shed light on the extent of global awareness and identify potential blind spots that hinder comprehensive understanding and effective action.